Learning organizations turning knowledge into actions - Goncalves, Marcus. (2012 digital library., 2012)
In a world that's facing economic recession, more and more professionals, teams, organizations, and inter-organizational networks are facing the need to restructure and renew themselves with the primary purpose of profitably trading their knowledge to add even higher value to their bottom line. Knowledge management has become a key strategic asset for the 21st century economy, and for every organization that values knowledge, it must invest in developing the best strategy for identifying, developing, and applying the knowledge assets it needs to succeed; it must strive to become a learning organization. To remain competitive every organization must invest in creating and implementing the best knowledge networks, processes, methods, tools, and technologies. This will enable them to learn, create new knowledge, and apply the best knowledge much faster. The aim of this book is to provide readers with key information necessary to become more successful with knowledge creating, transfer, and management, ultimately turning themselves and their organizations into a learning organization.